2020
DOI: 10.1177/2045125320954992
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for the effectiveness or safety of over-the-counter cannabidiol products

Abstract: Over the past 5 years, public interest in the potential health benefits of cannabidiol (CBD) has increased exponentially, and a wide range of over-the-counter (OTC) preparations of CBD are now available. A substantial proportion of the population appears to have used these products, yet the extent to which they are effective or safe is unclear. We reviewed the evidence for whether CBD has significant pharmacological and symptomatic effects at the doses typically found in OTC preparations. We found that most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 106 publications
(121 reference statements)
2
25
0
Order By: Relevance
“…This study showed increased connectivity within the executive control network; usually conceived as a network subserving attentional and cognitive processes involved in task engagement. Cannabidiol also may be a negative allosteric modulator at CB1 receptors (Laprairie et al, 2015;Chesney et al, 2020), and here we show increases in connectivity in the associative striatum; the region of the striatum most associated with cognitive functions and brain regions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study showed increased connectivity within the executive control network; usually conceived as a network subserving attentional and cognitive processes involved in task engagement. Cannabidiol also may be a negative allosteric modulator at CB1 receptors (Laprairie et al, 2015;Chesney et al, 2020), and here we show increases in connectivity in the associative striatum; the region of the striatum most associated with cognitive functions and brain regions.…”
Section: Discussionsupporting
confidence: 56%
“…THC is thought to exert its effects primarily by partial agonism at the CB1 receptor (Pertwee, 2008). CBD has less well understood and more complex pharmacological effects, including negative allosteric modulation at the CB1 receptor (Chesney et al, 2020), reducing reuptake of anandamide, and action on GPR55, μ-opioid, and 5-HT1A receptors (Pertwee, 2008). CBD has antipsychotic, (Leweke et al, 2012; McGuire et al, 2018), anxiolytic (Bergamaschi et al, 2011a) and anti-addictive (Hindocha et al, 2018; Hurd et al, 2019; Freeman et al, 2020) properties, and therefore has broadly oppositional neuropsychopharmacological effects to THC (Curran et al, 2016; Gunasekera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, careful examination of whether the influence of CBD on the immune system could exacerbate viral infection is required (reviews [ 64 , 65 ]). Indeed, viral, fungal infections and pneumonia infections are listed among the side effects of CBD [ 166 , 167 , 168 , 169 ]. Moreover, it has to be considered that CBD, which was found to have a pro-oxidative effect in one preclinical study ([ 83 ]; Table 1 ), might even aggravate the feared cytokine storm.…”
Section: Opportunities Challenges and Pitfalls Of Cannabidiol Usementioning
confidence: 99%
“…Unfortunately, these products may be of questionable quality, are not subject to appropriate safety controls and are characterized by unknown CBD content. There is little evidence of the pharmacological activity or health benefits of non-commercial CBD preparations [ 54 , 167 ]. Importantly, people taking non-commercial preparations on their own should be very careful due to the possibility of dangerous consequences, such as respiratory depression following, for example, CBD gummy ingestion [ 170 ] or CBD oil overdose [ 171 ].…”
Section: Opportunities Challenges and Pitfalls Of Cannabidiol Usementioning
confidence: 99%
See 1 more Smart Citation